Capacitive deionization of water (review) - Volfkovich, Yurii (My University, 2018)
The method of capacitive deionization of water (CDI) is to pump brackish water or seawater though an electrochemical cell, where certain potential difference is kept between carbon electrodes, which are characterized by high specific surface area. This method is sufficiently more attractive from the economical point of view in comparison with other desalination techniques, particularly with reverse osmosis that is widely used in industry. Different modifications of CDI have been developed, for instance, membrane capacitive deionization of water (MCDI) with cation and anion exchange membranes, CDI with ion-selective carbon electrodes, CDI with flow electrodes, CDI with Na-intercalating electrodes, CDI with cation-exchange and anion exchange mixed membrane of mosaic structure, which is used instead of conventional porous separator.
Keywords: capacitive deionization; mosaic membrane; carbon electrode; Na-intercalating electrode; membrane capacitive deionization; ємнісна деіонізація; мозаїчна мембрана; вугільний електрод; Na-iнтеркалюючий електрод; мембранна ємнісна деіонізація